Corrosion-resistant aluminum alloy with anti-exfoliation corrosion grade of N grade

By optimizing chemical composition and preparation process in Al-Zn-Mg-based aluminum alloy, especially increasing the content of Zn and Mg and adopting dual-stage homogenization and hot extrusion, the problem of difficult to take into account both tensile strength and corrosion resistance in the prior art is solved, and the effect of the peeling corrosion resistance level reaching N level and the tensile strength is greater than 780MPa.

CN119753457AActive Publication Date: 2025-04-04CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510038842.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-04
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

While the existing Al-Zn-Mg aluminum alloys have increased their tensile strength, their peeling corrosion sensitivity is increased, making it difficult to meet the requirements of high strength and high corrosion resistance at the same time.

Method used

By optimizing chemical composition in Al-Zn-Mg alloys, especially increasing the content of Zn and Mg, and adopting dual-stage homogenization treatment, hot extrusion, dual-stage solid solution and peak aging treatment in the preparation process, the use of Cu elements is avoided to improve corrosion resistance.

Benefits of technology

It has achieved ultra-high strength aluminum alloys with a peeling corrosion resistance level of N and tensile strength of 780MPa, meeting the requirements of ultra-high strength aluminum alloys in aerospace and transportation equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753457A_ABST
    Figure CN119753457A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of aluminum alloy materials, and provides an aluminum alloy with the tensile strength exceeding 780 MPa and the exfoliation corrosion grade N and a preparation method of the aluminum alloy. The aluminum alloy comprises the following chemical components in percentage by weight: 10.0-12.0% of Zn, 2.5-3.5% of Mg, 0.08-0.25% of Zr, 0.03-0.10% of Ti, less than or equal to 0.10% of Fe, less than or equal to 0.10% of Si, less than or equal to 0.05% of single other impurities, less than or equal to 0.15% of total impurities and the balance of Al. The preparation method comprises the following steps: burdening according to alloy components, and casting through a water-cooling mold to obtain an alloy round ingot with a required specification; carrying out two-stage homogenization process treatment and extrusion process molding; after two-stage solid solution and T6 peak aging, the tensile strength exceeds 780 MPa, and the anti-exfoliation corrosion grade is N grade; and the prepared plate can be widely applied to lightweight parts in the fields of aerospace, transportation, weapons and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal materials, and relates to an aluminum alloy and a preparation method thereof, and specifically to a preparation method of an ultra-high-strength aluminum alloy extruded plate with a tensile strength exceeding 780 MPa and an exfoliation corrosion resistance grade of N. Background Art

[0002] Al-Zn-Mg aluminum alloys have the advantages of low density, high strength and toughness, and low cost. They are structural materials with great application prospects in aerospace, navigation, military industry, and rail transportation. With the expansion of applications to offshore, industry, and atmosphere, the corrosion resistance and mechanical properties of traditional Al-Zn-Mg alloys have gradually failed to meet the design requirements of components. How to maintain good corrosion resistance while having high tensile strength has become a key problem in the development of Al-Zn-Mg alloys. Adding Cu elements to Al-Zn-Mg alloys for microalloying can promote the formation of clusters in the early stage of aging and increase the volume fraction of the strengthening phase, significantly affecting the type, morphology, and distribution of the precipitated phase, thereby improving the mechanical properties of the alloy. Many studies have shown that adding Cu elements to Al-Zn-Mg aluminum alloys can increase the hardness and tensile strength of the alloy, but at the same time increase the exfoliation corrosion sensitivity of the alloy (the exfoliation level is generally EB level and below), which limits the wide application of Al-Zn-Mg alloys.

[0003] In order to increase the strength and corrosion resistance of Al-Zn-Mg alloy, people have tried a series of solutions, such as: Patent application CN118497566A involves a lightweight, high modulus, high toughness and corrosion resistant aluminum alloy material, characterized in that the aluminum alloy contains: Mg 5.0~7.9wt%, Zn 2.2~4.6wt%, Li 0.5~1.9wt%, and at least one of Mn, Ti, Zr, Sc and Er with a total content not exceeding 0.7wt%, and the rest is Al and inevitable impurities, wherein each impurity element is ≤0.25wt% and the total is ≤0.50wt%. The preparation process adopted is: using ingot as raw material, homogenizing heat treatment and / or preheating, then adopting hot deformation, and then adopting solid solution treatment and aging to obtain high-quality products. In the best performance case disclosed in the embodiment, the tensile strength of the product is 569MPa and the exfoliation grade is N level.Patent application CN119082564A relates to a high-strength and corrosion-resistant A-Zn-Mg-Cu alloy, which includes the following mass percentage components: Cu2.0~2.5%, Mg 2.0~2.8%, Zn 6.0~6.8%, Zr0.05~0.1%, Be0.05~0.1%, Fe≤0.05%, Si≤0.03%, and the balance is aluminum and non-removable impurities; The high-strength and corrosion-resistant Al-Zn-Mg-Cu alloy is prepared by the following process: A. Smelting: using aluminum, magnesium, zinc, aluminum-copper master alloy, aluminum-zirconium master alloy, and aluminum-beryllium master alloy as raw materials; weighing the raw materials according to the composition ratio, loading them into a smelting furnace, and heating and melting; B. Refining, impurity removal, and degassing: After the metal melt is completely alloyed, adding an impurity remover into the alloy melt for slag aggregation, At the same time, argon gas is introduced for 10 to 20 minutes, an appropriate amount of hexachlorohexane is added, the mixture is allowed to stand, slag is removed, and the above operation is repeated 2 to 3 times. Then the aluminum alloy melt is allowed to stand for more than 20 minutes. C. Pouring: After the aluminum alloy melt is refined, impurity-removed, and degassed, the melt temperature is maintained at 730±5°C, poured into a mold, and cooled and solidified to obtain an ingot. D. Single-stage homogenization heat treatment: The ingot obtained in step C is heated to 465±5°C, and kept at this temperature for 12 to 36 hours, then removed from the furnace and air-cooled to room temperature. E. Hot rolling: The homogenized ingot obtained in step D is heated to 420±5°C and kept at this temperature for 60 to 120 minutes, and then multiple passes of hot rolling are performed to the set thickness of the alloy. During rolling, the pass reduction rate is controlled to be 5 to 20%, and the total reduction rate is controlled to be 75 to 85%. Annealing at 420±5℃ between rolling passes; air cooling and / or water cooling to room temperature after rolling; isothermal deformation workpiece; F. Heat treatment: first carry out solid solution treatment, heat the isothermal deformation workpiece to 465±5℃, keep it warm for 90~150min, and water quench it after it is taken out of the furnace; then carry out T74 double-stage aging treatment; T74 double-stage aging is: heat the solid solution treated part to 120~130℃ and keep it warm for 6-7h, then heat it to 175~185℃ and keep it warm for 7~8h, and then water quench it to room temperature after it is taken out of the furnace. The homogenization treatment is a single-stage homogenization heat treatment, the heating rate is 10~15℃ / min, the homogenization temperature is 465± 5℃, the holding time is 20~28h, and the strength of the obtained product is 585MPa and the intergranular corrosion is level 1.In order to further improve the strength of the product, patent application CN118880134A has developed an Al-Zn-Mg alloy with a strength of up to 800MPa. The alloy includes the following chemical components in weight percentage: Zn 10~12%, Mg2.5%~3.5%, Cu 0.9~2.2%, Zr 0.2%~0.25%, Cr 0%~0.1%, Ni 0%~0.1%, Fe≤0.1%, Si≤0.1%, other impurities individually ≤0.05%, total amount ≤0.15%, the balance is Al, and the rare earth content is less than 0.005%, the contents of Cr and Ni cannot be zero at the same time, but the patent does not involve the corrosion resistance of the product.

[0004] At present, there are few reports on corrosion-resistant aluminum alloys with an exfoliation corrosion resistance grade of N and a tensile strength greater than or equal to 740 MPa. Summary of the invention

[0005] The present invention is proposed on the basis of patent application CN118880134A in order to further improve the corrosion resistance of the product and ensure its strength.

[0006] The present invention discloses a corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N, which comprises the following chemical components by mass percentage: Zn 10.0-12.0%, Mg 2.5%-3.5%, Zr 0.08-0.25%, Ti 0.03-0.10%, Fe ≤ 0.10%, Si ≤ 0.10%, other impurities individually ≤ 0.05%, the total amount ≤ 0.15%, and the balance is Al; the corrosion-resistant aluminum alloy has an exfoliation corrosion resistance grade of N and a tensile strength greater than or equal to 740 MPa; The corrosion-resistant aluminum alloy is prepared by the following steps: Step 1: preparing the ingredients according to the above chemical composition and weight percentage requirements, and casting the aluminum alloy ingot through a water-cooled mold; Step 2: The ingot obtained in step 1 is treated according to a two-stage homogenization process, specifically as follows: the first stage homogenization temperature is 400-450°C, and the holding time is 8-16h; the second stage homogenization temperature is A°C, and the second stage homogenization treatment time is 30-48h; the holding time is 20-60h; after the ingot homogenization is completed, it is taken out and air-cooled; the value of A is 460-475°C; Step 3: After the ingot obtained in step 2 is peeled, hot extrusion is performed with an extrusion ratio of 20-50.

[0007] Step 4: The plate obtained in step 3 is subjected to a double-stage solid solution and peak aging treatment, as follows: the first-stage solid solution temperature is B℃, and the holding time is 1h-2h; the second-stage solid solution temperature is C℃, and the holding time is 20-45min; water quenching is performed after the solid solution stage, and peak aging treatment is performed after quenching; the peak aging temperature is 110-130℃, and the holding time is 16-32h; the value of B is 450-470, the value of C is 475-490, and B <C、A<C。

[0008] Preferably, the chemical composition of the alloy contains high content of Zn and Mg, and the weight percentages are: Zn 10.0-12.0%, Mg 2.5%-3.5%. In the present invention, the Zn content is not less than 10wt%, the Mg content is not less than 2.5%, and no Cu element is contained, which provides the necessary conditions for achieving ultra-high strength under peak aging state and having super strong exfoliation corrosion resistance in combination with subsequent extrusion and heat treatment processes.

[0009] As a further preferred embodiment, the present invention provides a corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N, which includes the following chemical components, by mass percentage: Zn 11-11.5%, Mg 2.8-3.3%, Zr 0.1-0.15%, Ti 0.03-0.07%, Fe ≤ 0.10%, Si ≤ 0.10%, other impurities individually ≤ 0.05%, total ≤ 0.15%, and the balance is Al.

[0010] As a further preferred embodiment, the present invention provides a corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N, which includes the following chemical components, measured by mass percentage: Zn 11.2%, Mg 3.2%, Zr 0.12%, Ti 0.05%, Fe ≤ 0.10%, Si ≤ 0.10%, other impurities individually ≤ 0.05%, total ≤ 0.15%, and the balance is Al.

[0011] The present invention adopts a special two-stage solid solution, in which the second stage solid solution temperature exceeds the over-firing temperature (that is, slightly higher than the over-firing temperature), so that more insoluble second phases are dissolved into the matrix, and the strengthening effect is further improved in combination with the hot extrusion process.

[0012] In the present invention, the reason why C is greater than A and B is that the second-stage solid solution temperature is higher than the homogenization and first-stage solid solution temperatures, so that the insoluble second phase at the A / B temperature is dissolved into the matrix, thereby increasing the supersaturation of the alloy after quenching.

[0013] As a further preferred embodiment, B <A<C。

[0014] Preferably, in the step 1, an aluminum alloy ingot is obtained by water-cooled mold casting, and the ingot size has a diameter of Φ110-130 mm.

[0015] Preferably, in the extrusion process of step three, the extrusion temperature is 410-430° C., more preferably 413-417° C., and the extrusion ratio is 26-28.

[0016] Preferably, the first stage solution temperature is 450-470°C, and the holding time is 80-100 minutes; the second stage solution temperature is 475-482°C, more preferably 480°C, and the holding time is 28-32 minutes. Because the temperature of the second stage aging is higher than the overburning temperature, its time must be strictly controlled, and its temperature cannot be too high. As a further preference, the solution process in step 4 adopts a two-stage enhanced solution process, which is as follows: The first stage solution temperature is 463-468℃, and the holding time is 80-100min; the second stage solution temperature is 478-482℃, more preferably 480℃, and the holding time is 28-32min. Because the temperature of the second stage aging is higher than the overburning temperature, its time must be strictly controlled, and its temperature cannot be too high.

[0017] Preferably, water quenching is adopted after the solution treatment in step 4 is completed, the quenching time is less than 5s, and the quenching temperature is room temperature; the peak aging temperature is 115-125°C, and the holding time is 20-28h.

[0018] After optimization, the present invention has a tensile strength of greater than 788 MPa, a yield strength of greater than 786 MPa, an elongation of greater than 5.0%, and an exfoliation corrosion grade of N level in the peak aging state product.

[0019] The product obtained by the present invention fully meets the requirements of existing aerospace and transportation equipment for ultra-high-strength aluminum alloys, and also meets the requirements of the future new generation of aerospace technology.

[0020] The present invention provides a corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N and a tensile strength greater than or equal to 740 MPa under the coordination of components and preparation process; the product obtained by the present invention after optimization has an exfoliation corrosion resistance grade of N and a tensile strength greater than or equal to 780 MPa.

[0021] The present invention must avoid the use of copper, otherwise the product's ability to resist exfoliation corrosion will be significantly reduced. The present invention, without copper and with the action of appropriate amounts of Zr and Ti combined with a large amount of zinc, can ensure that the product has high strength while also obtaining a product with extremely superior anti-exfoliation corrosion performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The exfoliation corrosion results of the alloy T6 peak aging state obtained in Comparative Example 1 for 48h; Figure 2 The exfoliation corrosion results of the alloy T6 peak aging state obtained in Comparative Example 2 for 48h; Figure 3 The exfoliation corrosion results of the alloy T6 peak aging state obtained in Comparative Example 3 for 48h; Figure 4 The exfoliation corrosion results of the alloy T6 peak aging state obtained in Example 1 for 48h; Figure 5 The exfoliation corrosion results of the alloy T6 peak aging state obtained in Comparative Example 4 for 48h; Figure 6 This is the exfoliation corrosion result of the alloy obtained in Example 2 at T6 peak aging state for 48h. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution, features and advantages of the embodiments of the present invention clearer, a clear and complete description will be given below in combination with the technical solution of the embodiments.

[0024] Comparative Example 1: The preparation process steps of the alloy are as follows: (1) The alloy ratio is Zn 11.0%, Mg 3.0%, Cu 0.5%, Zr 0.12%, Ti 0.05%; according to the above weight percentage, 99.99% high-purity Al ingot, pure Zn ingot, pure Mg ingot, Al-Cu master alloy, Al-Zr master alloy, Al-Ti-B wire are used; the measured composition is: Zn 11.3%, Mg 3.2%, Cu 0.57%, Zr 0.12%, Ti 0.04; (2) Melting in a high-temperature resistance furnace at a melting temperature of 730-780°C; After the metal is completely melted, it is continuously stirred and a refining agent is added. The refining is carried out in three batches at a refining temperature of 760°C; After refining, it is allowed to stand for 30 minutes and the temperature is maintained at 740°C; After sufficient standing, casting is performed. The ingot is cast using a water-cooled mold. During the casting process, the cooling water is kept flowing fully. After casting, an aluminum alloy ingot with a diameter of Φ120 mm is obtained; (3) The ingot is subjected to a two-stage homogenization treatment, and the homogenization process is as follows: the first-stage homogenization temperature is 440°C, and the holding time is 12 hours; the second-stage homogenization temperature is 470°C, and the holding time is 36 hours; (4) After homogenization, the ingot is taken out and air-cooled; (5) Peel the homogenized ingot, and the diameter of the ingot after peeling is Φ98mm; (6) Select a mold to extrude the ingot, the extrusion temperature is 415 ° C, and the extrusion ratio is 27; (7) The extruded sheet is subjected to a two-stage solid solution and peak aging treatment, wherein the first stage solid solution temperature is 465°C and the holding time is 90 min; the second stage solid solution temperature is 480°C and the holding time is 30 min; (8) After the solution treatment, water quenching is carried out and peak aging treatment is performed. The aging temperature is 120°C and the aging time is 24 h.

[0025] The peak aging exfoliation corrosion performance and tensile properties of the alloy obtained in Comparative Example 1 are as follows: Figure 1 As shown in Table 1, where σ b is the tensile strength, σ 0.2 is the yield strength and δ is the elongation.

[0026]

[0027] The resulting product has an exfoliation corrosion resistance grade of EC.

[0028] Comparative Example 2: The preparation process steps of the alloy are as follows: (1) The alloy ratio is Zn 7.0%, Mg 2.8%, Cu 1.0%, Zr 0.12%, Ti 0.05%; according to the above weight percentage, 99.99% high-purity Al ingot, pure Zn ingot, pure Mg ingot, Al-Zr master alloy, Al-Ti-B wire are used; the measured composition is: Zn 7.0%, Mg 2.74%, Zr 0.12%, Ti 0.05%; (2) Melting in a high-temperature resistance furnace at a melting temperature of 730-780°C; After the metal is completely melted, it is continuously stirred and a refining agent is added. The refining is carried out in three batches at a refining temperature of 760°C; After refining, it is allowed to stand for 30 minutes and the temperature is maintained at 740°C; After sufficient standing, casting is performed. The ingot is cast using a water-cooled mold. During the casting process, the cooling water is kept flowing fully. After casting, an aluminum alloy ingot with a diameter of Φ120 mm is obtained; (3) The ingot is subjected to a two-stage homogenization treatment, and the homogenization process is as follows: the first-stage homogenization temperature is 440°C, and the holding time is 12 hours; the second-stage homogenization temperature is 470°C, and the holding time is 36 hours; (4) After homogenization, the ingot is taken out and air-cooled; (5) Peel the homogenized ingot, and the diameter of the ingot after peeling is Φ98mm; (6) Select a mold to extrude the ingot, the extrusion temperature is 415 ° C, and the extrusion ratio is 27; (7) The extruded sheet is subjected to a two-stage solid solution and peak aging treatment, wherein the first stage solid solution temperature is 465°C and the holding time is 90 min; the second stage solid solution temperature is 480°C and the holding time is 30 min; (8) After the solution treatment, water quenching is carried out and peak aging treatment is performed. The aging temperature is 120°C and the aging time is 24 h.

[0029] The peak aging exfoliation corrosion performance and tensile properties of the alloy obtained in Comparative Example 2 are as follows: Figure 2 As shown in Table 2, where σ b is the tensile strength, σ 0.2 is the yield strength and δ is the elongation.

[0030]

[0031] The resulting product has an anti-scaling corrosion grade of EB.

[0032] Comparative Example 3: The preparation process steps of the alloy are as follows: (1) The alloy ratio is Zn 7.0%, Mg 2.0%, Cu 0.5%, Zr 0.12%, Ti 0.05%; according to the above weight percentage, 99.99% high-purity Al ingot, pure Zn ingot, pure Mg ingot, Al-Cu master alloy, Al-Zr master alloy, Al-Ti-B wire are used; the measured composition is: Zn 6.9%, Mg 2.1%, Cu 0.4%, Zr 0.12%, Ti 0.05%; (2) Melting in a high-temperature resistance furnace at a melting temperature of 730-780°C; After the metal is completely melted, it is continuously stirred and a refining agent is added. The refining is carried out in three batches at a refining temperature of 760°C; After refining, it is allowed to stand for 30 minutes and the temperature is maintained at 740°C; After sufficient standing, casting is performed. The ingot is cast using a water-cooled mold. During the casting process, the cooling water is kept flowing fully. After casting, an aluminum alloy ingot with a diameter of Φ120 mm is obtained; (3) The ingot is subjected to a two-stage homogenization treatment, and the homogenization process is as follows: the first-stage homogenization temperature is 440°C, and the holding time is 12 hours; the second-stage homogenization temperature is 470°C, and the holding time is 36 hours; (4) After homogenization, the ingot is taken out and air-cooled; (5) Peel the homogenized ingot, and the diameter of the ingot after peeling is Φ98mm; (6) Select a mold to extrude the ingot, the extrusion temperature is 415 ° C, and the extrusion ratio is 27; (7) The extruded sheet is subjected to single-stage solution treatment and peak aging treatment, wherein the solution temperature is 465°C and the holding time is 120 min; (8) After the solution treatment, water quenching is carried out and peak aging treatment is performed. The aging temperature is 120°C and the aging time is 24 h.

[0033] The peak aging tensile properties of the alloy obtained in Comparative Example 3 are shown in Table 3, where σ b is the tensile strength, σ 0.2 is the yield strength and δ is the elongation.

[0034]

[0035] The resulting product has an anti-scaling corrosion grade of EA.

[0036] Embodiment 1: The preparation process steps of the alloy are as follows: (1) The alloy ratio is Zn 11.0%, Mg 3.0%, Zr 0.12%, Ti 0.05%; according to the above weight percentage, 99.99% high-purity Al ingot, pure Zn ingot, pure Mg ingot, Al-Zr master alloy, Al-Ti-B wire are used; the measured composition is: Zn 11.2%, Mg 3.2%, Zr 0.12%, Ti 0.05%, Fe ≤ 0.10%, Si ≤ 0.10%, other impurities individually ≤ 0.05%, total ≤ 0.15%, and the balance is Al.

[0037] (2) Melting in a high-temperature resistance furnace at a melting temperature of 730-780°C; After the metal is completely melted, it is continuously stirred and a refining agent is added. The refining is carried out in three batches at a refining temperature of 760°C; After refining, it is allowed to stand for 30 minutes and the temperature is maintained at 740°C; After sufficient standing, casting is performed. The ingot is cast using a water-cooled mold. During the casting process, the cooling water is kept flowing fully. After casting, an aluminum alloy ingot with a diameter of Φ120 mm is obtained; (3) The ingot is subjected to a two-stage homogenization treatment, and the homogenization process is as follows: the first-stage homogenization temperature is 440°C, and the holding time is 12 hours; the second-stage homogenization temperature is 470°C, and the holding time is 36 hours; (4) After homogenization, the ingot is taken out and air-cooled; (5) The ingot after homogenization is peeled, and the diameter of the ingot after peeling is Φ98mm; (6) Select a mold to extrude the ingot, the extrusion temperature is 415 ° C, and the extrusion ratio is 27; (7) The extruded sheet is subjected to a two-stage solid solution and peak aging treatment, wherein the first stage solid solution temperature is 465°C and the holding time is 90 min; the second stage solid solution temperature is 480°C and the holding time is 30 min; (8) After the solution treatment, water quenching is carried out and peak aging treatment is performed. The aging temperature is 120°C and the aging time is 24 h.

[0038] The peak aging exfoliation corrosion performance and tensile properties of the alloy obtained in Example 1 are as follows: Figure 3 As shown in Table 4, where σ b is the tensile strength, σ 0.2 is the yield strength and δ is the elongation.

[0039]

[0040] It can be seen from the above results that the present invention can produce an ultra-high-strength aluminum alloy with a tensile strength exceeding 780 MPa and an exfoliation corrosion resistance grade N, wherein the tensile strength reaches 788 MPa and the elongation reaches 5.3%.

[0041] During the technical exploration process, other parameters and steps were tried that were consistent with Example 1, except that the second-stage solution temperature in the two-stage solution was 480°C and the holding time was 45 minutes. It was found that the mechanical properties of the product decayed too quickly.

[0042] Comparative Example 4 (1) The alloy ratio is Zn 12.9%, Mg 3.6%, Zr 0.12%, Cu 1.0%, and Ti 0.05%. According to the above weight percentage, 99.99% high-purity Al ingots, pure Zn ingots, pure Mg ingots, Al-Zr master alloys, and Al-Ti-B wires are used.

[0043] The tensile strength of the obtained product is 765MPa, and the elongation is 4.2%; the exfoliation corrosion resistance grade is ED grade.

[0044] Example 2 During the technical exploration process, other parameters and steps were tried that were consistent with Example 1, with the difference that in the two-stage solid solution, the first stage solid solution was at 450°C and kept warm for 90 minutes, and the second stage solid solution temperature was 480°C and kept warm for 30 minutes. It was found that the mechanical properties of the product also decayed too quickly.

[0045] The tensile strength of the obtained product is 740 MPa, and the elongation is 2.9%; the anti-exfoliation corrosion grade is about N level. From the pictures, its effect is worse than that of the product obtained in Example 1.

[0046] Comparative Example 5 Other conditions are consistent with those in Example 1, except that: 11.2% Zn, 3.0% Mg, 1.0% Cu, 0% Ti, tensile strength 765 MPa, yield strength 720 MPa, elongation 4.5%, and exfoliation corrosion resistance grade EC.

[0047] The above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes can be made based on the above descriptions, and it is not necessary and impossible to list all the embodiments here. The changes derived therefrom are still within the scope of protection of the present invention.

Claims

1. A corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N, characterized in that: The following chemical components are included in percentage by mass: Zn 10.0-12.0%, Mg 2.5%-3.5%, Zr 0.08-0.25%, Ti 0.03-0.10%, Fe ≤ 0.10%, Si ≤ 0.10%, other impurities ≤ 0.05% each, ≤ 0.15% in total, and the balance is Al; the corrosion-resistant aluminum alloy has an exfoliation corrosion resistance grade of N and a tensile strength of greater than or equal to 740 MPa; The corrosion-resistant aluminum alloy is prepared by the following steps: Step 1: preparing the ingredients according to the above chemical composition and weight percentage requirements, and casting the aluminum alloy ingot through a water-cooled mold; Step 2: The ingot obtained in step 1 is treated according to a two-stage homogenization process, specifically as follows: the first stage homogenization temperature is 400-450°C, and the holding time is 8-16h; the second stage homogenization temperature is A°C, and the second stage homogenization treatment time is 30-48h; the holding time is 20-60h; after the ingot homogenization is completed, it is taken out and air-cooled; the value of A is 460-475°C; Step 3: After peeling the ingot obtained in step 2, hot extrusion is performed with an extrusion ratio of 20 to 50; Step 4: The plate obtained in step 3 is subjected to a double-stage solid solution and peak aging treatment, as follows: the first-stage solid solution temperature is B℃, and the holding time is 1h-2h; the second-stage solid solution temperature is C℃, and the holding time is 20-45min; water quenching is performed after the solid solution stage, and peak aging treatment is performed after quenching; the peak aging temperature is 110-130℃, and the holding time is 16-32h; the value of B is 450-470, the value of C is 475-490, and B <C、A<C。 2. The corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N according to claim 1, characterized in that: Calculated by mass percentage, it includes the following chemical components: Zn 11-11.5%, Mg 2.8-3.3%, Zr 0.1-0.15%, Ti 0.03-0.07%, Fe ≤ 0.10%, Si ≤ 0.10%, other impurities individually ≤ 0.05%, total ≤ 0.15%, and the balance is Al.

3. The corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N according to claim 1, characterized in that: Calculated in mass percentage, it includes the following chemical components: Zn 11.2%, Mg 3.2%, Zr 0.12%, Ti 0.05%, Fe ≤ 0.10%, Si ≤ 0.10%, other impurities individually ≤ 0.05%, total ≤ 0.15%, and the balance is Al.

4. The corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N according to claim 1, characterized in that: B <A<C。 5. The corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N according to claim 1, characterized in that: In the step 1, an aluminum alloy ingot is obtained by casting with a water-cooled mold, and the ingot has a diameter of Φ110-130 mm.

6. The corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N according to claim 1, characterized in that: In the step 3, the extrusion temperature during the extrusion process is 410-430° C., more preferably 413-417° C., and the extrusion ratio is 26-28.

7. The corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N according to claim 1, characterized in that: The solution process of step 4 adopts a two-stage strengthening solution process, which is as follows: The first stage solution temperature is 450-470°C, and the holding time is 80-100 min; the second stage solution temperature is 475-482°C, more preferably 480°C, and the holding time is 20-60 min.

8. The corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N according to claim 1, characterized in that: After the solution treatment in step 4 is completed, water quenching is performed, the quenching time is less than 5 seconds, and the quenching temperature is room temperature; the peak aging temperature is 115-125° C., and the holding time is 20-28 hours.

9. The corrosion-resistant aluminum alloy with an exfoliation corrosion resistance grade of N according to claim 1, characterized in that: The tensile strength of the peak aged product is greater than 788MPa, the yield strength is greater than 786MPa, the elongation is greater than 5.0%, and the exfoliation corrosion grade is N.

Citation Information

Patent Citations

  • High-strength corrosion-resistant Al-Zn-Mg-Cu-Zr-Be alloy and application thereof

    CN119082564A

  • Copper-free ultrahigh-strength aluminum alloy and preparation method thereof

    CN118166247A

  • Ultrahigh-strength aluminum alloy with tensile strength exceeding 800 MPa and preparation method of ultrahigh-strength aluminum alloy

    CN118880134A